Sled Pushing and Pulling to Enhance Speed Capability. Issue 4 (August 2019) - Cahill, Micheál J.; Cronin, John B.; Oliver, Jon L.; P. Clark, Kenneth; Lloyd, Rhodri S.; Cross, Matt R.
Abstract : ABSTRACT: RESISTED SPRINTING IN THE FORM OF SLED PUSHING AND PULLING ARE POPULAR TRAINING METHODS TO IMPROVE SPEED CAPABILITY, ALTHOUGH RESEARCH HAS BEEN BIASED TOWARD INVESTIGATING THE EFFECTS OF SLED PULLING. PRACTITIONERS NEED TO UNDERSTAND WHETHER THE SLED PUSH AND PULL OFFER DIFFERENTIAL TRAINING EFFECTS, AND HENCE THEIR UTILITY IN INFLUENCING SPRINT KINEMATICS AND KINETICS FOR TARGETED ADAPTATION. FURTHERMORE, THERE ARE A NUMBER OF RECENT DEVELOPMENTS IN LOADING AND ASSESSMENT THAT WARRANT DISCUSSION, GIVEN THE IMPACT OF THESE TECHNIQUES ON UNDERSTANDING THE LOAD-VELOCITY RELATIONSHIP AND OPTIMIZING HORIZONTAL POWER OUTPUT. FINALLY, SOME THOUGHTS REGARDING LOAD PRESCRIPTION ARE SHARED WITH THE READER. Abstract : Supplemental Digital Content is Available in the Text.